PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN STRUKTUR KEPEMILIKAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR): STUDI EMPIRIS PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BEI - Gustari, Rizki Asih; Kamaliah, Kamaliah; Afifah, Ulfa (LPPM Universitas Bina Bangsa, 2025)
This research aims to examine the influence of profitability, company size, and ownership structure on Corporate Social Responsibility (CSR) disclosure. The research population includes non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) in 2020-2023, with 76 companies selected as samples using a purposive sampling approach. The approach applied in this research is a quantitative approach, with data analysis using panel data regression using Eviews 12 software. The results show that profitability has a negative effect on CSR disclosure, company size has a positive effect on CSR disclosure, institutional ownership has a negative effect on CSR disclosure, while public ownership does not show a significant effect on CSR disclosure